Manajemen Ekstrakurikuler Dalam Meningkatkan Karakter Tanggung Jawab Peserta Didik - Marlina Andriani; Anggil Jufinda; Darsi Darsi; Joni Wilson Sitopu; Jenuri Jenuri; MS Viktor Purhanudin (Departement of Mathematics Education, 2023)
The focus of this research is the management of extracurricular activities in improving the character of students' responsibilities at SMP Negeri 7 Kerinci. The research questions are (1) how is the management of extracurricular activities in improving the character of the students' responsibilities at SMP Negeri 7 Kerinci?; (2) what are the supporting and inhibiting factors for extracurricular activities in improving the responsible character of students at SMP Negeri 7 Kerinci?; (3) what are the results of improving the character of student responsibilities at SMP Negeri 7 Kerinci through extracurricular management? The method in this thesis is qualitative with the type of field survey located at SMP Negeri 7 Kerinci. Collecting data using interviews, observation, and documentation. While the data analysis method uses three steps, namely data reduction, data presentation, and drawing conclusions. The research results show: (1) the management of extracurricular activities at SMP Negeri 7 Kerinci includes: first, extracurricular activity planning is carried out at the beginning of each new school year. What is planned is teachers, students, facilities and schedule of activities; second, the implementation of extracurricular activities is grouped into two, namely, compulsory extracurricular and elective extracurricular. Extracurricular activities run every day according to the schedule that has been prepared; third, Evaluation of extracurricular activities is carried out every three months. Things that are evaluated include the targets that have been set, such as the champion target the school wants to achieve; (2) Supporting factors in the implementation of extracurricular activities, namely facilities and infrastructure, funds, students, and mentor teachers who are competent in their fields. Factors hindering it are student attendance, lack of funds, and there is also the weather factor; (3) The results of the quality of the character of responsibility after the management of extracurricular activities are good and increasing. Judging from the educational process that runs smoothly, and thanks to the good management of extracurricular activities, carrying out tasks on time, disciplined and serious SMP Negeri 7 Kerinci can achieve non-academic achievements.